2022
DOI: 10.3390/children9030304
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of Parental Instability for Children Born Very Preterm and Impacts on Neurodevelopmental Outcomes at Age 12

Abstract: Caring for a child born preterm places significant emotional and financial burdens on family relationships. This paper examines (a) the extent to which children born very and extremely preterm are more likely to experience parental change/caregiver instability than children born full term, (b) predictors of parental change/s for preterm infants, and (c) whether exposure to parental change/caregiver instability increases child neurodevelopmental risk. Data were collected as part of a prospective longitudinal st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 50 publications
(52 reference statements)
0
11
0
Order By: Relevance
“…Around-the-clock care for the preterm infant, hospital visits, uncertain prognosis, and frequent stressful situations can lead to significant emotional exhaustion in the family. This has a negative impact on relationships and the well-being of the family [ 73 , 74 , 77 , 78 , 80 , 81 , 82 , 83 ].…”
Section: Influence Of Prematurity On the Mother And Familymentioning
confidence: 99%
See 4 more Smart Citations
“…Around-the-clock care for the preterm infant, hospital visits, uncertain prognosis, and frequent stressful situations can lead to significant emotional exhaustion in the family. This has a negative impact on relationships and the well-being of the family [ 73 , 74 , 77 , 78 , 80 , 81 , 82 , 83 ].…”
Section: Influence Of Prematurity On the Mother And Familymentioning
confidence: 99%
“…A total of 3161 tweets from parents of premature infants were analyzed. It was found that the COVID-19 pandemic and the associated restrictions, which affected parents’ contact with preterm infants, imposed significant emotional burdens on the studied group [ 76 , 80 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 ]. Health safety concerns: Mothers of premature infants have heightened concerns about their children’s health in the context of the pandemic.…”
Section: Influence Of the Covid-19 Pandemic On The Stressmentioning
confidence: 99%
See 3 more Smart Citations